O processamento prosódico gráfico de sentenças ambíguas na leitura silenciosa de surdos bilíngues - Francisca Maria Carvalho (2017)
We start from the proposal of Fodor (2002) that both syntactic structures as the prosodic are computed during silent reading. We examined the effect of prosodic marking graphical processing of silent reading of temporary ambiguous sentences as: When dogs attacked / a girl (,) / tore her dress / yellow, considering the integration syntax-prosody. We compare the silent reading time of the third fragment of temporary subordinate ambiguous sentences in written texts of the Portuguese language for deaf bilingual Libras/Portuguese. We assume that deaf people spend more time reading than listeners, but there would also be a difference as one disambiguator comma were or not present in the sentence. The experiment made up an online test of 108 subordinate temporary ambiguous sentences, in 6 conditions, through DMDX program. 18 deaf bilingual Libras/Portuguese and 18 listeners participated. There was no significant difference in the reading time of the third fragment of temporary subordinate ambiguous sentences between deaf and listeners; also, there was no significant difference with the use of the comma. There were differences between the means Late Closure (LC) and Early Closure (EC); Semantic Control (SC) and Early Closure (EC). There was no significant difference between the types of Late Closure (LC) and Semantic Coutrol (SC) sentence.